Ophthalmological impairment in patients with congenital cytomegalovirus infection - Salomè, Serena; Ciampa, Nicola; Giordano, Mariapaola; Raimondi, Raffaele; Capone, Eleonora; Grieco, Claudia; Coppola, Clara; Capasso, Letizia; Raimondi, Francesco (Frontiers in Pediatrics, 2023)
Backgroundː Congenital cytomegalovirus (cCMV) infection is a frequent cause of neurosensory impairment. Ocular abnormalities and visual impairment have been reported in a high percentage of symptomatic infants, whereas they are considered uncommon in asymptomatic ones. The paucity of data has made difficult to reach clear recommendations on the ophthalmological follow-up that should be provided. Methodsː 250 patients with cCMV infection (123 symptomatic) were enrolled and underwent a series of age-appropriate ophthalmologic, audiologic, and neurodevelopmental examinations from 2002 to 2022. Resultsː Funduscopic abnormalities were identified at onset in 16/123 (13%) symptomatic infants and in none of the asymptomatic ones (p <0.001). Chorioretinitis lesions were the most common findings (10/16 cases), while the others showed retinal scars. Lesions were bilateral in 4 patients. No later onset retinal lesions were detected, nor in symptomatic or in asymptomatic children. Five of the 16 (31.5%) symptomatic and none of the asymptomatic subjects showed visual impairment al the last evaluation (p <0.001). All patients with unfavorable outcome had also neurological impairment. Among symptomatic patients, ocular lesions were associated with central nervous system (CNS) pathological findings in prenatal ultrasonography (p 0.05) and with clinical signs of CNS involvement at birth (p 0.046). No correlation was found with the type of maternal infection and pathological neuroimaging. Conclusionsː Chorioretinal lesions are a fairly common finding at birth in neonates with symptomatic cCMV, often associated with long term visual impairment. Asymptomatic infants do not show ophthalmological abnormalities in the short or long term. This information is relevant both to parental counseling and to cost-effective patient management.